Toxoplasma gondii infection blocks the development of allergic airway inflammation in BALB/c mice - Fenoy, Ignacio Martín (2009)
There is a link between increased allergy and a reduction of some infections in western countries. Epidemiological data also show that respiratory allergy is less frequent in people exposed to orofaecal and foodborne microbes such as Toxoplasma gondii. Infection with T. gondii induces a strong cell-mediated immunity with a highly polarized T helper type 1 (Th1) response in early stages of infection. Using a well-known murine model of allergic lung inflammation, we sought to investigate whether T. gondii infection could modulate the susceptibility to develop respiratory allergies. Both acute and chronic infection with T. gondii before allergic sensitization resulted in a diminished allergic inflammation, as shown by a decrease in bronchoalveolar lavage (BAL) eosinophilia, mononuclear and eosinophil cell infiltration around airways and vessels and goblet cell hyperplasia. Low allergen-specific immunoglobulin (Ig)E and IgG1 and high levels of allergen-specific IgG2a serum antibodies were detected. A decreased interleukin (IL)-4 and IL-5 production by lymph node cells was observed, while no antigen-specific interferon-γ increase was detected. Higher levels of the regulatory cytokine IL-10 were found in BAL from infected mice. These results show that both acute and chronic parasite infection substantially blocked development of airway inflammation in adult BALB/c mice. Our results support the hypothesis that T. gondii infection contributes to protection against allergy in humans. © 2008 British Society for Immunology.